2011
DOI: 10.1370/afm.1250
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effects and the Common Cold: A Randomized Controlled Trial

Abstract: PURPOSE We wanted to determine whether the severity and duration of illness caused by the common cold are infl uenced by randomized assignment to openlabel pills, compared with conventional double-blind allocation to active and placebo pills, compared with no pills at all. METHODSWe undertook a randomized controlled trial among a population with new-onset common cold. Study participants were allocated to 4 parallel groups: (1) those receiving no pills, (2) those blinded to placebo, (3) those blinded to echinac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 68 publications
(76 reference statements)
3
36
1
Order By: Relevance
“…A previous study considered that the placebo effect was derived from factors included in a social, cultural and clinical context, rather than from the sham interventions per se (44). Other studies (42,45,46) demonstrated that a placebo effect was a complexity resulting from psychological, social and cultural background factors, as well as real physiological responses.…”
Section: A Powerful Placebo Effect May Results In a Potential Biasmentioning
confidence: 99%
“…A previous study considered that the placebo effect was derived from factors included in a social, cultural and clinical context, rather than from the sham interventions per se (44). Other studies (42,45,46) demonstrated that a placebo effect was a complexity resulting from psychological, social and cultural background factors, as well as real physiological responses.…”
Section: A Powerful Placebo Effect May Results In a Potential Biasmentioning
confidence: 99%
“…Patients with new onset colds were recruited from the community through newspaper advertisements, community talks, posters, direct mailings, emails, and wordof-mouth [49,50]. The prospective participants would call an advertised phone number and be screened for eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods and results are available elsewhere. 3,[8][9][10] Objective ARI Monitoring Nasal lavage was collected twice during the study, once at enrollment (day 1), and then again 2 days later (day 3). The NMI test is conducted by instilling a 5-mL aliquot of sterile isotonic medium into each nostril, followed by expression into a sterile container.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Although previously used in a moderately large randomized controlled trial, 3 the NMI measurement has yet to be validated. The present study tested the NMI for concurrent and predictive validity.…”
mentioning
confidence: 99%